Bridging health and nutritional benefits through staple rice (Webinar session 4) - Sreenivasulu, Nese (International Maize and Wheat Improvement Center, 2023)
The TAFSSA CGIAR Initiative is hosting a series of webinars to highlight research from South Asia on food security, sustainable healthy diets, farmer livelihoods and resilience, and land, air, and groundwater conservation. For the fourth webinar on March 28, Dr. Nese Sreenivasulu will present. Dr. Nese Sreenivasulu is the head of research center, provides scientific leadership for International Rice Research Institute (IRRI’s) research on grain quality and nutrition program deploying enabling technologies in the discipline of biochemistry, food science, genetics and genomics. He led the team involved in establishing regional capacity to establish Center of Excellence for Rice Value Addition (CERVA) at IRRI South Asia Regional Centre (ISARC) in India to offer frontier research platform with wide-array of services to support grain quality, nutrition and food safety aspects.